2019
DOI: 10.3389/fpls.2019.00981
|View full text |Cite
|
Sign up to set email alerts
|

Straight From the Plastome: Molecular Phylogeny and Morphological Evolution of Fargesia (Bambusoideae: Poaceae)

Abstract: Fargesia is ecologically and economically important in mountainous forests. Many Fargesia species are also important sources of food for some endangered animals such as the giant panda. Recent molecular phylogenetic analyses have revealed Fargesia as a polyphyletic group despite some unclear lineage affinities. In the present study, we reconstructed the phylogeny of Fargesia and its allies, including Thamnocalamus, Arun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 75 publications
(225 reference statements)
0
9
0
Order By: Relevance
“… 2019 ; Zhou et al. 2019 ). To date, however, only a small amount of complete plastid genomes has been reported for members of Phyllostachys , such as P. propinqua (Wu and Ge 2012 ), P. sulphurea (Gao and Gao 2016 ), P. nigra , and P. edulis (Zhang et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 2019 ; Zhou et al. 2019 ). To date, however, only a small amount of complete plastid genomes has been reported for members of Phyllostachys , such as P. propinqua (Wu and Ge 2012 ), P. sulphurea (Gao and Gao 2016 ), P. nigra , and P. edulis (Zhang et al.…”
mentioning
confidence: 99%
“…Information from chloroplast genome sequences has been extensively applied in understanding interspecific relationship (Ma et al 2014;Li et al 2019;Zhou et al 2019). To date, however, only a small amount of complete plastid genomes has been reported for members of Phyllostachys, such as P. propinqua (Wu and Ge 2012), P. sulphurea (Gao and Gao 2016), P. nigra, and P. edulis (Zhang et al 2011).…”
mentioning
confidence: 99%
“…Based on vegetative traits, both Fargesia and Yushania were divided into two sections (Yi, 1986, 1988; Yi et al, 2008). However, the plastome‐based phylogeny in our analyses revealed that these key morphological characters for genus and section delimitation are not objective, as suggested by previous molecular studies (Triplett & Clark, 2010; Zeng et al, 2010; Zhang et al, 2012, 2016, 2018; Attigala et al, 2016; Zhou et al, 2019). From our plastome phylogenetic trees, we inferred that Fargesia initially colonized along the border of Tibet and Yunnan (V‐ Fargesia ‐alpine) with subsequent dispersal to the Qinling mountains (V‐ Fargesia 2), then together with Yushania , spread to mountain areas of the east Himalaya, Hengduan Mountains, and southern China (V‐FY).…”
Section: Discussionmentioning
confidence: 51%
“…To date, the phylogenetic framework of Arundinarieae has been established by using plastid phylogenomic analyses (Ma et al, 2014, 2017; Attigala et al, 2016). Nevertheless, no study has focused on these two species‐rich genera except Zhou et al (2019), which included 20 plastomes of Fargesia and revealed that Fargesia is a polyphyletic group and divided into eight clades.…”
Section: Introductionmentioning
confidence: 99%
“… Fargesia is a polyphyletic genus and could be divided into three or four clades based on plastome sequences ( Zhang et al 2018 ; Zhou et al 2019 ) and double-digested restriction enzyme-associated DNA sequencing (ddRAD-seq) data ( Ye et al 2019 ). F. viridis was classified as belonging to V- Fargesia 4 clade based on the phylogenetic results of ddRAD-seq analyses ( Ye et al 2019 ), but no conclusion could be made for its position on the plastome phylogeny.…”
Section: Discussionmentioning
confidence: 99%